MATURATION AND SPAWNING OF LIZARD FISHES (SAURIDA SPP. ) FROM NORTHWESTERN PART OF BAY OF BENGAL - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
Ova-diameter frequencies indicate that the spawning period in 5. tumbil isprotracted, extending from October to Marcti, with the peak in November-December and that the eggs are shed in 5 or 6 batches. The minimum size atfirst maturity and size at 50% maturity in female have found to be 260 and300 nun in total length, respectively. The fecundity estimates ranged from 37,569to 2,14,981 eggs in the size range 290-430 mm. Ova counts per gram of theovary were calculated for estimating the number of eggs spawned in differentbatches. A plot of fecundity values against length showed an exponential relationshipof the form, F = AL while the relationship between the fecundity andweight of fish is expressed by a linear regression equation of the form Y = A + BX.The available data indicates that the spawning and maturation in S. undosquamismay be similiar to that of S. tumbil The differences between specimens of S.tumbil. from Waltair, Mangalore and the East China and Yellow seas in respectof the size of the ova, spawning period and other characters are given